KOMPARASI MODEL COLLABORATIVE COLLECTION DEVELOPMENT DAN JUST-IN-TIME COLLECTION DEVELOPMENT PADA PERPUSTAKAAN PENDIDIKAN - Santi Puji Astuti; Sri Rohyanti Zulaikha (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
This study aims to answer the question of how the application of collaborative and just-in-time model collection development and how the comparison of the two models that have been applied to educational libraries. The method used in this research is a critical review method with a literature study approach. The writer made comparation and analyze between two articles which adopted in different model of collection development. The research findings are as follows: 1) The collaborative collection development model utilizes library networks to save budgets and accelerate collection availability, while the just-in-time collection development model applies a responsive access-based collection development approach. This policy is to provide the right and fast collection and save funds. 2) The difference between these two models is that the collaborative model requires a network so as to facilitate the process of both procurement together in order to create budget savings, while the just-in-time collection development is a single model that does not really require a network so that it has absolute autonomy.